Analisis Pengakuan Pendapatan Berdasarkan Psak 72 Pada PT Mitra Sukses Mamminasata - Andi Zulfakar Yudha; Intan Sadha Patulak Marewa (CV. ITTC INDONESIA, 2022)
This study aims to determine whether the revenue recognition of PT Mitra Sukses Mamminasata fit or not with PSAK 72. This study’s using descriptive qualitative approach. This study indicate that the company recognized their revenue accordance to PSAK 72, with five special steps in recognition process: (1) identify the contract with customer; (2) identify obligation; (3) determine the price; (4) allocate the transaction price; (5) recognize the revenue.